Antibacterial potential of Urtica dioica and Lavandula angustifolia extracts against methicillin resistant Staphylococcus aureus isolated from diabetic foot ulcers - Zenão, S. (2020)
Despite the antibacterial potential of plant extracts against several bacterial infections, until now, no major studies have been published about the effect of lavender and nettle leaves against methicillin-sensitive and methicillin-resistant strains of Staphylococcus aureus (MSSA and MRSA, respectively). Thus, the authors studied their antibacterial potential against MSSA and MRSA from diabetic foot ulcers in order to find alternatives to the systematic use of antibiotics. Phenolic acids, flavonoids, flavones and flavonols were extracted from lavender and nettle leaves and characterized by HPLC-DAD/Vis. Disc diffusion assay and minimum inhibitory concentration (MIC) were used to assess their antibacterial activity. A direct association between the high content of hydroxycinnamic acids (chlorogenic acid, caffeic acid, rosmarinic acid) and flavonoids (quercetin) and decreasing bacterial growth activity was noted. The fact that lavender and nettle are rich in hydroxycinnamic acids and quercetin seems to explain the high antibacterial potential of these plant and the differences between them.